0556 Sex-Specific Relationship Between Anxiety and Autonomic Nervous System Dysfunction in Obstructive Sleep Apnea. (27th May 2020) - Pal, A; Akey, M A; Chatterjee, R; Aguila, A P; Martinez, F; Aysola, R; Macey, P M
Abstract: Introduction: Cardiovascular co-morbidities in obstructive sleep apnea (OSA) are hard to treat, perhaps due to autonomic nervous system (ANS) dysfunction. In OSA, intermittent hypoxia and poor tissue oxygen perfusion damage endothelial and nervous tissue, potentially underlying the dysfunction. Moreover, OSA is strongly associated with anxiety, which is independently associated with ANS dysfunction. We assessed sex-specific relationships between anxiety and cardiovascular markers of ANS dysfunction in OSA. Methods: We studied people diagnosed with OSA and healthy controls. We collected 5 minutes of wakeful resting ECG, continuous non-invasive blood pressure, and respiration data. We calculated heart rate (HR), heart rate variability (HRV; sympathetic-vagal balance related to brainstem ANS output), mean arterial blood pressure (MAP), beat-to-beat MAP variability (BPV; related to peripheral autonomic function) and breathing rate (BR). We analyzed these measures with a multivariate regression model of anxiety symptoms (generalized anxiety disorder; GAD-7 scores), sex, and group (OSA vs. control), age/BMI/AHI covariates, and Bonferroni-corrected post-hoc comparisons ( p ≤0.05). Results: We analyzed 64 subjects (32 OSA: AHI [mean±SEM] 24±4events/hour, 12 female, age 52±21years, BMI 33±2kg/m2; 32 control: 19 female, age 46±2; BMI 26±1). We observed significant main effects of anxiety, BMI, AHI, sex on HRV, but only group on BPV; post-hoc comparisons revealed high BPV only in OSA females. Secondary analyses included classifying by anxiety symptoms (GAD-7≥5), showing only OSA females with anxiety had higher BPV. Males showed higher HRV. AHI and anxiety were positively correlated with HRV in OSA males. AHI was negatively correlated with BR in OSA females. Conclusion: We observed higher anxiety associated with higher BPV in OSA, especially in females. Unexpectedly, BR was lower in OSA females; longer breaths may have led to the greater BPV. Higher HRV in males complicated by OSA severity and anxiety could be related to higher sympathetic tone. The slightly older control group may have influenced the findings. Overall, our findings suggest anxiety in OSA is associated with peripheral and centrally-mediated autonomic dysfunction, but in a sex-specific manner. Support: National Institutes of Health R56-NR-017435 and RO1-HL-135562.